The relationship of school principals' leadership styles and emotional intelligence on school effectiveness / Sueb Ibrahim - Ibrahim, Sueb (2016)
Research on effective leadership and emotional intelligence is growing. Yet, there still remains a gap on the relationships that exist between leadership and emotional intelligence especially on school effectiveness. Utilizing these connections, the main aim of this study was to identify the relationship of principals' leadership style and emotional intelligence and on school effectiveness. This study utilized both quantitative and qualitative approaches in gathering the data for this study. A total of 115 school principals participated in this study for the quantitative analysis while 8 school principals participated in the qualitative analysis. A focus group interview was also conducted for the development of the School Effectiveness Indicator Instrument (SEII) that measured the level of school effectiveness. Two other instruments that were adapted for this study were Bass and Avolio's Multifactor Leadership Questionnaire (MLQ5X Form) that identified the principals' leadership styles, and Mayer - Salovey - Caruso Emotional Intelligence Test (MSCEIT) was used to operationalize emotional intelligence. The findings of this study are as follow. First, it indicated that the principals perceived themselves as exhibiting a highly transformational leadership style as compared to the other two leadership styles, namely transactional and laissez- faire. Second, it revealed that the principals assessed themselves as demonstrating more on managing emotions as compared to the other three emotional branches namely perceiving emotions, facilitating emotions, and understanding emotions. Third, it depicted that over the three years (2007 -2009), the schools in Sarawak occupied the three lower bands of school namely Band 3 (Fairly Low), Band 4 (Satisfactory) and Band 5 (High). Fourth, it revealed that there was a weak but significant relationship between the transactional leadership relationship and emotional intelligence while the other two leadership styles did not indicate any significant relationship. Fifth, there was no evidence to believe that principals' leadership style scores was significantly related to school effectiveness. Sixth, the findings indicated the existence of significant relationships between EI branches and school effectiveness. Seventh, there was no significant relationship between gender and leadership style scores. Eighth, findings indicated no significant relationship between salary grade and leadership style scores and finally, in terms of gender and salary grade, there was no significant difference in the EI as a whole. From the findings of the study, training and other professional development programmes may be more precisely formulated to empower secondaryschool principals in Sarawak and also in Malaysia as a whole. It also proposes some dimensions and indicators for school effectiveness that can be used as guidelines in measuring the level of school effectiveness in Malaysian schools.